Inhibitory Effect of Artemisinin on Testosterone Propionate Induced Benign Prostatic Hyperplasia - Solanki, Ayushi; Patel, Sandip; Solanki, Nilay; Shah, Umang (Current Drug Discovery Technologies, 2021)
Background: Benign prostate hyperplasia [BPH] is an abnormal growth of prostate observed commonly in elderly males. Artemisinin has been reported to reduce the levels of testosterone. Objective: This study is designed to evaluate the efficacy of Artemisinin on testosterone propionate [TP] induced benign prostate hyperplasia. Materials and Methods: Male Wistar albino rats [n=24] were separated into four groups of six rats each. Group I served as control and distilled water using tween 80 as an emulsifying agent was administered subcutaneously. BPH was induced by testosterone propionate 3mg/kg [Group II], S.C. daily for 28 days. Group III was BPH + Finasteride treated group (10mg/kg orally for 28 days) and BPH + Artemisinin treated group (Group IV) (50 mg/kg orally for 28 days). Result: The study results showed significantly high levels of serum prostatic acid phosphatase (PAP), lactate dehydrogenase (LDH) and an elevation in prostate weight and prostatic index in Group II (BPH) when compared with Group I. The histopathological examination showed an increase in the epithelial proliferation of prostatic cells with involutions protruding into the lumen in BPH group when compared to the normal group. Treatment with Artemisinin (50 mg/kg) reduced the levels of PAP, LDH, prostate weight and prostatic index to a significant extent and restored the histoarchitectural features of the cells. Conclusion: The present study concludes that Artemisinin is efficacious in testosterone propionate induced BPH. This could be attributed, at least partly, to its anti-inflammatory property or its role in testosterone level reduction or as a Vitamin D receptor modulator.
Keywords: Vitamin D receptor modulator